Pasture-finishing of bison improves animal metabolic health and potential health-promoting compounds in meat - Stephan van Vliet; Amanda D. Blair; Lydia M. Hite; Jennifer Cloward; Robert E. Ward; Carter Kruse; Herman A. van Wietmarchsen; Nick van Eekeren; Scott L. Kronberg; Frederick D. Provenza (Journal of Animal Science and Biotechnology, 2023)
Abstract Background With rising concerns regarding the effects of red meat on human and environmental health, a growing number of livestock producers are exploring ways to improve production systems. A promising avenue includes agro-ecological practices such as rotational grazing of locally adapted ruminants. Additionally, growing consumer interest in pasture-finished meat (i.e., grass-fed) has raised questions about its nutritional composition. Thus, the goal of this study was to determine the impact of two common finishing systems in North American bison—pasture-finished or pen-finished on concentrates for 146 d—on metabolomic, lipidomic, and fatty acid profiles of striploins (M. longissimus lumborum). Results Six hundred and seventy-one (671) out of 1570 profiled compounds (43%) differed between pasture- and pen-finished conditions (n = 20 animals per group) (all, P < 0.05). Relative to pasture-finished animals, the muscle of pen-finished animals displayed elevated glucose metabolites (~ 1.6-fold), triglycerides (~ 2-fold), markers of oxidative stress (~ 1.5-fold), and proteolysis (~ 1.2-fold). In contrast, pasture-finished animals displayed improved mitochondrial (~ 1.3-fold higher levels of various Krebs cycle metabolites) and carnitine metabolism (~ 3-fold higher levels of long-chain acyl carnitines) (all P < 0.05). Pasture-finishing also concentrated higher levels of phenolics (~ 2.3-fold), alpha-tocopherol (~ 5.8-fold), carotene (~ 2.0-fold), and very long-chain fatty acids (~ 1.3-fold) in their meat, while having lower levels of a common advanced lipoxidation (4-hydroxy-nonenal-glutathione; ~ 2-fold) and glycation end-product (N6-carboxymethyllysine; ~ 1.7-fold) (all P < 0.05). In contrast, vitamins B5, B6, and C, gamma/beta-tocopherol, and three phenolics commonly found in alfalfa were ~ 2.5-fold higher in pen-finished animals (all P < 0.05); suggesting some concentrate feeding, or grazing plants rich in those compounds, may be beneficial. Conclusions Pasture-finishing (i.e., grass-fed) broadly improves bison metabolic health and accumulates additional potential health-promoting compounds in their meat compared to concentrate finishing in confinement (i.e., pen-finished). Our data, however, does not indicate that meat from pen-finished bison is therefore unhealthy. The studied bison meat—irrespective of finishing practice—contained favorable omega 6:3 ratios (< 3.2), and amino acid and vitamin profiles. Our study represents one of the deepest meat profiling studies to date (> 1500 unique compounds), having revealed previously unrecognized differences in animal metabolic health and nutritional composition because of finishing mode. Whether observed nutritional differences have an appreciable effect on human health remains to be determined. Graphical abstract